Does integrated science education improve scientific literacy? - Laura Tamassia; Renaat Frans (JETEN, 2014)
In Flanders, a choice has been made for the integrated school subject ‘Natural Sciences’, in ‘science for all’ secondary school trajectories, and for the three separate subjects biology, physics and chemistry, in trajectories for the future scientist and technician. In the framework of the Flemish project ‘Practice-oriented reviews of research in subject matter teaching’, we have performed a study with the aim of investigating, on the basis of the existing literature, whether there is currently any scientific evidence that the integration of biology, chemistry and physics in the secondary school subject Natural Sciences improves student results for scientific literacy. The followed methodology is based on the general principles of the systematic review, but with the final goal of producing a text useful for teacher educators, teacher students and teachers, and not a technical review only readable by researchers in science education. The main result of this study is that there is currently no scientific evidence of the effectiveness of integration for scientific literacy. The main conclusion for practice is that integration alone does ‘no magic’. This implies that intellectual freedom remains for teachers and teacher educators within the framework of the subject Natural Sciences on how to structure instruction. In the light of this, we stress the importance of educating future teachers to be aware of the current debate and to form their own opinion.